BUILD EMPLOYEE PERFORMANCE - Harras, Hadyati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The purpose of this study was to determine the effect of work complacent and motivation of job on the employees working performance either partially or simultaneously. The object research carried out to the employee stamp of PT. Bank Panin BSD Tangerang Selatan. Design research conducted in the preparation of this is associative quantitative that aims to determine the influence between two or more deeply variables describe or reveal a problem, situation, event or revealing fact as they are deeply and try to find a solution or solutions to problems. The results showed that work content based on partial test was positive and significant effect on the achievement capability of 51,7% and then work arousal also was positive and significant effect on performance of 52,6%. The result of determinate coefficient (R2) of 63,8% can be summed up the effect of the variable job satisfaction and work motivation toward employees performance where the influence are positive. The results of calculation for 41,458 F-value further consultation with the F-table with dk = k numerator and denominator dk = (nk-1) with a 5% error level the importance of the F table = 3,18. Provisions applicable for F-value greater than F-table (41,458 > 3,18), it can be stated that the multiple correlation is significant. Thus the null hypothesis (H0) that states there is no effect between work satiation and work motivation influence on employees performance is rejected, while the alternative hypothesis (Ha) are accepted